Cucurbitacin B inhibits human breast cancer cell proliferation through disruption of microtubule polymerization and nucleophosmin/B23 translocation - Duangmano,S. (BioMed Central, 2015)
Background: Cucurbitacin B, an oxygenated tetracyclic triterpenoid compound extracted from the Thai medicinal plant Trichosanthes cucumerina L., has been reported to have several biological activities including anti-inflammatory, antimicrobial and anticancer. Cucurbitacin B is great of interest because of its biological activity. This agent inhibits growth of various types of human cancer cells lines.Methods: In this study, we explored the novel molecular response of cucurbitacin B in human breast cancer cells, MCF-7 and MDA-MB-231. The growth inhibitory effect of cucurbitacin B on breast cancer cells was assessed by MTT assay. The effects of cucurbitacin B on microtubules morphological structure and tubulin polymerization were analyzed using immunofluorescence technique and tubulin polymerization assay kit, respectively. Proteomic analysis was used to identify the target-specific proteins that involved in cucurbitacin B treatment. Some of the differentially expressed genes and protein products were validated by real-time RT-PCR and western blot analysis. Cell cycle distributions and apoptosis were investigated using flow cytometry.Results: Cucurbitacin B exhibited strong antiproliferative effects against breast cancer cells in a dose-dependent manner. We show that cucurbitacin B prominently alters the cytoskeletal network of breast cancer cells, inducing rapid morphologic changes and improper polymerization of the microtubule network. Moreover, the results of 2D-PAGE, real-time RT-PCR, and western blot analysis revealed that the expression of nucleophosmin/B23 and c-Myc decreased markedly after cucurbitacin B treatment. Immunofluorescence microscopy showed that cucurbitacin B induced translocation of nucleophosmin/B23 from the nucleolus to nucleoplasm. Treatment with cucurbitacin B resulted in cell cycle arrest at G2/M phase and the enhancement of apoptosis.Conclusions: Our findings suggest that cucurbitacin B may inhibit the proliferation of human breast cancer cells through disruption of the microtubule network and down-regulation of c-Myc and nucleophosmin/B23 as well as the perturbation in nucleophosmin/B23 trafficking from the nucleolus to nucleoplasm, resulting in G2/M arrest. © 2012 Duangmano et al.; licensee BioMed Central Ltd.